Geoprocessamento e planta de valores genéricos - uma discussão das tendências e vantagens da associação dessas tecnologias - Montanha, Enaldo Pires (Universidade Federal de São Carlos, 2005)
This work aims at to subsidize the urban administrator, in the implantation of the Plant of Generic Values, using tools of Geoprocessamento, with the purpose to bring more efficiency and equity in the collection of municipal tributes. In the majority of the Brazilian cities, the venal values of the property are calculated by zones of fiscal abrangência, without efficiency of the application of the methods determinístico or probabilist, already normalized. The use of a georreferenciada cartographic base, associated to the one System of Information Geographic, will facilitate the application of these methods, besides providing to precision in the analysis and the maintenance of the data of the place of the evaluation and of its around.
Keywords: Planejamento urbano; Sistemas de informação geográfica; Modelos georeferenciados; Valor venal; Cadastro imobiliário; ENGENHARIAS::ENGENHARIA CIVIL